Influence of Organoclay on the Flame Retardancy and Thermal Insulation Property of Expandable Graphite/Polyurethane Foam - Nhung Hac Thi; Duy Linh Pham; Nguyen Thi Hanh; Ho Thi Oanh; Thi Hai Yen Duong; Thanh Nhan Nguyen; Nguyen Duc Tuyen; Dinh Long Phan; Ha Thu Trinh; Ha Tran Nguyen; Tung Ngo Trinh; Mai Ha Hoang (Journal of Chemistry)
The rigid polyurethane foams (RPUFs) filled with organoclay cloisite 20A and expandable graphite (EG) were prepared by the one-step expanding foam method. Flame behavior, mechanical properties, and thermal conductivity of the composites were investigated. The vertical burning test (UL-94V) and limiting oxygen index (LOI) showed that the flame retardancy was increased proportionally with the content of EG in PU composite. However, the presence of EG filler impaired the thermal insulation and the compressive strength of the composite. In this report, we proved that organoclay could improve the compressive strength, thermal insulation, and flame retardancy of EG/polyurethane composites. This work can contribute to the development of environment-friendly flame-retardant products for green growth.